2021
DOI: 10.3390/nu13072176
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Pediatrics. A Review and Practical Guide

Abstract: The potential benefit of the administration of probiotics in children has been studied in many settings globally. Probiotics products contain viable micro-organisms that confer a health benefit on the host. Beneficial effects of selected probiotic strains for the management or prevention of selected pediatric conditions have been demonstrated. The purpose of this paper is to provide an overview of current available evidence on the efficacy of specific probiotics in selected conditions to guide pediatricians in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 146 publications
(222 reference statements)
0
21
0
3
Order By: Relevance
“…Compared with no treatment, low or very low evidence represented that the following probiotics could shorten the duration of diarrhea: S. boulardii (MD = −0.95 day; 95%CI, −1.33, −0.58), LGG (MD = −1.57 day; 95%CI, −2. 13 1). B. lactis had the highest probability of reducing the duration of diarrhea when compared with no treatment (Supplementary Material Table S27).…”
Section: Duration Of Diarrheamentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with no treatment, low or very low evidence represented that the following probiotics could shorten the duration of diarrhea: S. boulardii (MD = −0.95 day; 95%CI, −1.33, −0.58), LGG (MD = −1.57 day; 95%CI, −2. 13 1). B. lactis had the highest probability of reducing the duration of diarrhea when compared with no treatment (Supplementary Material Table S27).…”
Section: Duration Of Diarrheamentioning
confidence: 99%
“…However, it cannot halt the progression of diarrhea, nor address microflora imbalance, pathogen clearance, and environmental enteric dysfunction [11,12], all of them may be addressed by probiotics. Probiotics were recommended as adjuncts to effectively alleviate and treat diarrhea by clinical practice guidelines and numerous studies [7,[13][14][15]. Traditional pairwise meta-analysis only focused on one probiotic and failed to find the most effective probiotic [6,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Современные представления о возможностях лечебно-профилактического использования пробиотиков (и пробиотических продуктов) у детей с респираторными инфекциями также неоднозначны [18][19][20][21][22][23][24][25].…”
Section: пробиотикиunclassified
“…Observational and experimental studies from community settings have shown that gut microbiota immaturity or dysbiosis is associated with risk of development of acute malnutrition and linear growth failure in children [ 2 , 3 , 4 , 5 ]. Probiotics are one of the commonly used products to promote healthy gut microbiomes, encompassing a USD 54 billion industry around the globe [ 6 , 7 ]. Probiotics are defined as live microorganisms that, when administered in adequate amounts, confer a health benefit to the host [ 8 ].…”
Section: Introductionmentioning
confidence: 99%